A modification to the cross slitting method for measuring two components of residual stresses. (February 2017) - Mahmoudi, AH; Hasani, AR
Residual stresses measurement techniques are constantly modified and progressed. There have been many residual stresses measurement methods developed and practiced by researchers. Slitting method is one of the destructive techniques that can measure residual stresses deep within the components. However, the conventional slitting method can only measure the component of residual stress normal to the cut plane. Furthermore, the cross slitting has been developed to measure two components of residual stresses simultaneously. In the current research, a modification to the cross slitting method is proposed to enhance the accuracy of the technique. The samples were prepared exactly similar to previous study and were quenched at different temperatures to create different levels of residual stresses in order to compare the outcomes. The proposed modification was examined both numerically and experimentally. The results confirmed the success of the modification in reducing the errors. Results from experiments and predictions agreed well.